Understanding Corruptors’ Imagination Concerning Money Through Their Metaphors - Dhuha Hadiyansyah; Didin Nuruddin Hidayat (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThis study illustrates the imagination of corrupt politicians from the Prosperous Justice Party (PKS) about money through observing the metaphors they use to replace the word